(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
What advantages does play have in the classroom? Playful learning fosters social relationships and connectivity in kids, all of which are critical for a child's academic perseverance, enthusiasm for learning, and self-efficacy. All kindergarteners need to play in order to learn. It can fill in a child's developmental gaps and be academically demanding.